Hybrid diabetes in a patient with latent autoimmune diabetes in adults and genetic markers of predisposition to type 2 diabetes and obesity. Сlinical observation - A. V. Vetrova; M. M. Orlova; N. E. Kolobanova (Лечащий Врач)
We present a case report of a 40-year-old Caucasian man who was diagnosed with type 2 diabetes mellitus at the age of 27. In his case, the patient took oral hypoglycemic drugs for 6 months, but then insulin therapy was started because glycemic goals were not achieved. In order to verify the right type of diabetes after 6 years of the onset of disease, the patient was tested on the main immunological and genetic markers of diabetes mellitus. This observation period clearly demonstrated the "typical" course of LADA. The main signs of LADA are – gradual decreasing in the level of C-peptide, starting insulin therapy after 6 months from the onset of diabetes. LADA is associates with positive autoimmune markers (GAD-antibodies) in blood samples. In the case of our patient we saw the "classical" development of LADA. According to modern datas, pathogenesis of different types of diabetes is based on multiple variants of β-cell damage, which can lead to unique course of treatment and manifestation of macroand microvascular complications. It means that different gene combination can cause clinical symptoms of diabetes which can not be classified only on 1 or 2 type of diabetes. The idea of "hybrid" forms of diabetes has long attracted attention, since their pathogenesis may be based on various types of damage to β-cells, which affects the course, prognosis, and clinical tactics. On the one side we see typical LADA signs. On the other case, physicians wanted to see the prognosis of the disease, especially predict the same case of LADA in patient’s family. The patient underwent genetic testing for 9 main genes, mutations in which are responsible for predisposition to obesity and type 2 diabetes. According to the results of this study, the patient had a heterozygous mutation in the genes: TCF7L2, CDKAL1, CDKN2A/2B. The patient revealed a hybrid form of LADA, combining both immunological markers of LADA (positive antibodies to GAD), as well as genetic markers of type 2 diabetes mellitus (mutation in the genes TCF7L2, CDKAL1, CDKN2A/2B). The number of patients with the onset of diabetes mellitus at a young age and the absence of a sign of absolute insulin deficiency are increasing. Genetic, immunological tests can help patients to achieve glycemic goals and prevent macroand microvascular complications